Classics of public administration - Shafritz, Jay M.; Hyde, Albert C. (Fort Worth : Harcourt Brace College Publishers, 1997)
Be assured the editors are not so bold as to assert that these are the classics of public administration. This field is so diverse that there can be no such list .
Part One. Early Voices and first quarter century -- Part Two. The new deal to mid-century -- Part Three. The 1950s and 1960s -- Part Four. The 1970s and 1980s -- Part Five. The 1990s tradition to the next century.
Includes bibliographical references.
Keywords: PUBLIC ADMINISTRATION